FACTORES ASOCIADOS A CARIES Y ENFERMEDAD PERIODONTAL EN MUJERES GESTANTES, BUCARAMANGA, 2001 (2018)
Purpose: A cross sectional study was done to determine the factors associated with caries and periodontal condition of pregnant women.Material and Methods: One hundred and forty nine women were examined in the city of Bucaramanga in a period of time between February to May, 2001. Sociodemographic variables in regard to gestation, diet, beliefs and oral health practices were evaluated as independent variables. The outcome was defined by COP index and CPITN index. Simple and multiple logistic regression were applied to evaluate the possible association by Odds Ratio (OR) and their 95% confidence interval.Results: The adjusted OR for COP was: age OR: 1.27 95% CI (1.15-1.41), social security OR: 0.04 CI 95% (0.006-0.27) and week of pregnancy OR: 0.93 CI 95% (0.87-0.99). The model for CPITN was: Hypertension OR: 11.8 CI 95% (1.14-121.3), deficient oral hygiene OR: 4.19 CI 95% (1.63-10.8), social security OR: 0.19 CI 95% (0.05-0.7) and high risk pregnancy OR: 0.27 CI 95% (0.07-0.98).Conclusions: These findings provide clear guidelines for the proposal of attendance programs, prevention of oral diseases programs and promotion of oral health programs for pregnant women.